2012
DOI: 10.1177/1533317512460564
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Cognitive Health

Abstract: Growing evidence suggests that healthy behaviors such as being physically active, having a heart healthy diet, and being socially involved may promote cognitive health. The United States has recently begun encouraging such behaviors for that purpose. To help evaluate the diffusion of this policy, we sought to measure a baseline of activity in this area. We examined Web sites of 156 large health care systems, the health departments of all 50 states and the 20 largest US cities, and 181 nationally accredited sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Over the last decade, governments and Alzheimer's International agencies have implemented public health campaigns targeting these modifiable lifestyle factors that impact upon brain health and cognition ( Centers for Disease Control and Prevention, 2007 , Laditka et al, 2012 , World Health Organisation, 2012 ). In Australia, the national ‘Mind Your Mind’ dementia risk prevention programme was one of the first initiatives to place dementia prevention in the context of maintaining overall health and wellbeing ( Connor, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, governments and Alzheimer's International agencies have implemented public health campaigns targeting these modifiable lifestyle factors that impact upon brain health and cognition ( Centers for Disease Control and Prevention, 2007 , Laditka et al, 2012 , World Health Organisation, 2012 ). In Australia, the national ‘Mind Your Mind’ dementia risk prevention programme was one of the first initiatives to place dementia prevention in the context of maintaining overall health and wellbeing ( Connor, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of surveys have been conducted across the United States ( Anderson et al, 2009 , Laditka et al, 2012 ) the United Kingdom ( McParland et al, 2012 , U.K. Health Forum, 2014 ) and Australia ( Low and Anstey, 2007 , Smith et al, 2014 ) to assess the public's knowledge of the modifiable determinants of cognitive health and dementia risk. Generally, these surveys have been undertaken in the context of developing public health strategies to prevent cognitive decline in older age.…”
Section: Introductionmentioning
confidence: 99%
“…The online format provides health services to older adults who otherwise would not receive them 17 . A review of health systems, public health departments, and senior centers also highlights that corroborating the study's findings, there is growing evidence to suggest that healthy behaviors, such as being physically active, eating a healthy diet, and being socially involved, can promote cognitive health 32 .…”
Section: Discussionmentioning
confidence: 62%
“…Growing evidence suggests that a healthy lifestyle could help seniors maintain their cognitive health (Laditka, Laditka, & Lowe, 2012). Indeed, studies have found that age-related cognitive decline might be lesser among seniors who are engaged in regular physical activities (Buchman, Wilson, & Bennett, 2008; Middleton, Mitnitski, Fallah, Kirkland, & Rockwood, 2008), such as brisk walking (Prohaska et al, 2009) or an extended training program (Lautenschlager et al, 2008).…”
Section: Introductionmentioning
confidence: 99%